Can Finance Drive the Green Energy Transition? A System-GMM Analysis of OECD Countries - Ulucay, Lale Kübra; Ünlü, Ulaş (International Journal of Energy Economics and Policy, 2025)
This study investigates how financial development (FD), foreign direct investment (FDI), and per capita carbon emissions (CO₂) influence renewable energy consumption (REC) in 23 OECD countries from 2000 to 2021. Using a dynamic panel data model, it examines the role of financial systems and cross-border capital flows in supporting the shift toward cleaner energy. To handle potential endogeneity and dynamic structure, the two-step System Generalized Method of Moments (System-GMM) estimator is applied, along with robustness checks using Difference-GMM and fixed-effects models. The results reveal three key insights. First, renewable energy consumption shows strong persistence, indicating that energy transitions evolve gradually. Second, financial development has a positive but modest impact on REC, implying that strong institutions and effective regulation are crucial for finance to promote green investment. Third, higher per capita CO₂ emissions are associated with lower REC, suggesting that fossil fuel–dependent economies face greater challenges in transitioning to renewables. Overall, both financial systems and FDI can act as catalysts for renewable energy adoption, yet their effectiveness depends on institutional quality and policy coherence. Strengthening green finance, carbon pricing mechanisms, and cross-border investment frameworks may accelerate the green transition in OECD countries.